2022
DOI: 10.1016/j.celrep.2022.110328
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of satellite glia in sympathetic and sensory ganglia

Abstract: Satellite glia are the major glial type found in sympathetic and sensory ganglia in the peripheral nervous system, and specifically, contact neuronal cell bodies. Sympathetic and sensory neurons differ in morphological, molecular, and electrophysiological properties. However, the molecular diversity of the associated satellite glial cells remains unclear. Here, using single-cell RNA sequencing analysis, we identify five different populations of satellite glia from sympathetic and sensory ganglia. We define thr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
50
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(73 citation statements)
references
References 95 publications
10
50
1
Order By: Relevance
“…In the adult PNS, BLBP expression is restricted to satellite glia and is not detected in Schwann cells based on single-cell RNA-sequencing analysis and characterization of Fabp7-CreER2- driven reporter mice ( Avraham et al, 2020 ). Using data sets from our recently published single-cell RNA-sequencing analysis of peripheral sympathetic and sensory ganglia from adult mice (postnatal days 30–45) ( Mapps et al, 2022 ), we found that BLBP ( Fabp7 ) is ~140-fold enriched in satellite glial cells compared to other ganglionic cell types ( Figure 1—figure supplement 1A ). Of note, Schwann cells are scarce in adult sympathetic ganglia compared to sensory ganglia based on single-cell RNA-sequencing analyses ( Mapps et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the adult PNS, BLBP expression is restricted to satellite glia and is not detected in Schwann cells based on single-cell RNA-sequencing analysis and characterization of Fabp7-CreER2- driven reporter mice ( Avraham et al, 2020 ). Using data sets from our recently published single-cell RNA-sequencing analysis of peripheral sympathetic and sensory ganglia from adult mice (postnatal days 30–45) ( Mapps et al, 2022 ), we found that BLBP ( Fabp7 ) is ~140-fold enriched in satellite glial cells compared to other ganglionic cell types ( Figure 1—figure supplement 1A ). Of note, Schwann cells are scarce in adult sympathetic ganglia compared to sensory ganglia based on single-cell RNA-sequencing analyses ( Mapps et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Using data sets from our recently published single-cell RNA-sequencing analysis of peripheral sympathetic and sensory ganglia from adult mice (postnatal days 30–45) ( Mapps et al, 2022 ), we found that BLBP ( Fabp7 ) is ~140-fold enriched in satellite glial cells compared to other ganglionic cell types ( Figure 1—figure supplement 1A ). Of note, Schwann cells are scarce in adult sympathetic ganglia compared to sensory ganglia based on single-cell RNA-sequencing analyses ( Mapps et al, 2022 ). To further ensure the cellular specificity of BLBP, we generated genetic reporter mice by crossing Fabp7-CreER2 mice with ROSA26 mEGFP mice ( Muzumdar et al, 2007 ), which drives expression of membrane-tagged EGFP ( Figure 1—figure supplement 1B ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Validation of tSC population using published NMJ bulk RNAseq data Published bulk RNA seq data containing nonmyelinating, synaptic glia of the neuromuscular junction (NMJ; Mapps et al, 2022) was downloaded and processed as follows: fastq files were aligned with STAR tool and count matrices generate via featureCounts using mouse genome annotation gencode M27. Count matrix was then analysed via DESeq2 pipeline, where the covariate to compare was FACS sorting of cells being S100β-GFP + or S100β-GFP + /NG2-dsRed.…”
Section: Comparative Validation Of Terminal Schwann Cells and Satelli...mentioning
confidence: 99%